A Conceptual Study on the Etiology of Criminality: Early Childhood Memory and Predisposition to Violence Criminal Behavior - Sayed Mothar, Syaripah Mohaizah; Md Isa, Noor Shamsarini; anuar, inda (Research in Management of Technology and Business, 2024)
This concept paper on the relationship between early childhood memories and violent criminal behaviour points out a severe gap in the present understanding of the development of such behaviour. It sets out to examine how far traumatic experiences in earlier life, in the form of serious instances of abuse, affect the possibilities of violent dispositions later in life by applying some of the key theories in psychology and sociology, such as Social Learning Theory and Neutralization Theory. In this mixed-method approach study, qualitative data shall be elicited by carrying out in-depth interviews with sentenced offenders and mental health professionals. Quantitative data shall be obtained from structured questionnaires and archival research. These findings will have the potential to contribute to crime reduction, enhance public safety, and support policymakers in crafting evidence-based approaches to foster a safer and more just society at a national and global level. The research is focused on exploring trends of childhood traumatic experiences and their influence on violent behaviour to develop proper prevention strategies, therapeutic interventions, and legislation aimed at mitigating the perpetration of heinous violent crimes, thereby promoting social well-being.